The Role of Energy in The World - Numonjonov Shokhzod Dilshodjon ugli; Ortigaliyeva Mubinakhon Anvarjon qizi (Genius Journals, 2023)
In this article, energy is an important component of development and growth. This leads to the emergence of investments, innovations and new industries, which are important engines of job creation, inclusive economic growth and general well-being for the entire economy. In this blog we covered the importance of energy, the current state of access to it, the importance of renewable energy, energy shocks and problems and the promotion of sustainable energy
Keywords: Energy; resource; technology; fuel